Prognostics and health management : a practical approach to improving system reliability using conditioned-based data /: a practical approach to improving system reliability using conditioned-based data. ([2019]) - (Industrial engineer), Goodman, Douglas; Hofmeister, James P; Szidarovszky, Ferenc
No abstract available